Antiinflamation Activity Test of Keji Beling (Strobilanthes crispa (L.) Blume) Leaves Extraction on White Mencites (Mus musculus) - Purba, Novandi; Lubis, Kholilah Putri (Jurnal FARMASIMED (JFM), 2024)
Background: Inflammation often occurs in According to data from WHO, 2004) the number of people with bone inflammation worldwide reached around 11.9 million people. In high-income countries, around 1.3 million people experience bone pain, while in low to middle-income countries, the prevalence reached 5.9 million. In Southeast Asia, there are 4.4 million people with arthritis. In North Sumatra, the prevalence of arthritis according to the diagnosis of health workers is 8.4%, while based on diagnosis or symptoms it reaches 19.2%. In Medan City, the prevalence based on the diagnosis of health workers is 5.1%, and based on diagnosis and symptoms it is 17.2%. The method used in this study is the formation of artificial edema on the soles of the feet of male white mice with 1% carrageenan induction. Testing the anti-inflammatory activity of keji beling leaf extract was carried out with 25 test animals divided into 5 treatment groups. The groups consisted of positive controls given sodium diclofenac at a dose of 6.5 mg/kgBW, negative controls given Na-CMC 0.5%, and three extract groups at doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW. The results showed that the percentage of inflammation in the five test groups decreased consistently from the 60th minute to the 360th minute after carrageenan induction. The highest percentage of inflammation was recorded at the 120th minute for the Na-CMC group, followed by the 100 mg/kgBW, 200 mg/kgBW, 300 mg/kgBW, and sodium diclofenac groups. The highest percentage of inflammation inhibition was obtained from the sodium diclofenac portion, followed by 300 mg/kgBW, 200 mg/kgBW, and 100 mg/kgBW. This shows that the good inhibition percentage is owned by EDKB 300 mg/kgBW continued sodium diclofenac, and EDKB 200 mg/kgBW and 100 mg/kgBW. This indicates that the sodium diclofenac portion and extract with doses of 100, 200, and 300 mg/kgBW have the power to function as anti-inflammatory agents, compared to the Na-CMC group which showed no effect.